Ethical Market Failure and Islamic Political Economy: A Framework for Digital Competition Governance - Mutadi Mutadi; Abdul Aziz; Dewi Fatmasari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Digital platform capitalism has restructured market coordination through data extraction, algorithmic governance, network effects, and ecosystem integration. Contemporary competition law, grounded in the consumer welfare paradigm, evaluates market conduct primarily through price-based metrics that obscure structural asymmetries. This article addresses the gap between allocative efficiency and structural justice by developing Ethical Market Failure (EMF)—a structural extension of classical market failure theory capturing infrastructural concentration, dependency locking, and distributive asymmetry in platform dominated economies. Integrating digital competition scholarship with Islamic political economy, the study employs the Maqasid alShariah framework as a normative evaluative architecture. The classical institution of hisbah is reinterpreted as a governance logic informing regulatory oversight. Using Indonesia as a semi analytical empirical anchor, the article demonstrates how subsidy driven expansion, gig labor absorption, and ecosystem consolidation generate long-term structural distortions despite short-term consumer gains. This study contributes to platform governance debates by situating consumer welfare within a broader justice sensitive institutional hierarchy.